Methods for correlated observations with applications to genetic association studies - Li, Shuo (2019)
Correlation is commonly present in genetic association studies and may yield incorrect inference when ignored. Hence, developing methods for properly analyzing correlated data is crucial. However, there is a lack of analytical tools to answer certain questions because existing methods are not applicable when some model assumptions are violated. In this thesis, we propose three methods for correlated phenotypes, particularly correlation arising from family data.